SAFETY AND SECURITY ASSESSMENT OF PURSE SEINER BASED AT NIZAM ZACHMAN OCEANIC FISHING PORT, JAKARTA - Ibrahim, Yudy; Solihin, Iin; Wahyu, Ronny Irawan; Mustaruddin (Departemen PSP IPB, 2025)
Ship safety issues are in the global spotlight, including on purse seine vessels based at the Nizam Zachman Jakarta Ocean Fisheries Port (PPSNZJ). This is due to the high number of ship accidents. There have been 11 (eleven) cases of ship sinking and fires in 2020-2022. This study uses a descriptive survey method through observation, interviews, and questionnaires. The determination of respondents was carried out by purposive sampling and data analysis was carried out descriptively quantitatively. The results of the study showed that most purse seine vessels had complied with the procedures and administration of fishing vessel safety and security standards with an average value of 95.73%, meaning very compliant. However, the completeness of work safety and security equipment such as helmets, gloves, and welding shields is still low, or only reaching an average of 45%. This means that awareness and implementation of work safety standards are not evenly distributed among ship owners and crew. Key words: assessment, compliance, occupational safety, purse seine